LEGAL ASPECTS OF THE REHABILITATION OF SEXUAL VIOLENCE VICTIMS DURING ARMED CONFLICTS - Tsymbaliuk, V. I.; Hryshko, V. I.; Sakhniuk, V. V. (Rehabilitation and Recreation, 2025)
Sexual violence in armed conflict is one of the most serious forms of violation of international law, with devastating consequences for victims and society as a whole. This article examines the historical development of the legal regulation of this problem, analyzes the jurisprudence of international tribunals, and considers modern mechanisms for prevention and holding perpetrators accountable. The role of Ukraine in shaping the national policy on the protection and rehabilitation of victims is considered, in particular, the legislative consolidation of their special status and the development of assistance mechanisms. The need for a comprehensive approach, including legal, social and medical mechanisms for supporting victims of sexual violence during armed conflicts, is substantiated. It has been established that an integrated approach to supporting victims of sexual violence, including medical, financial, and social services, is essential for ensuring justice and rehabilitation in the post-conflict period. Legislative initiatives contribute to the creation of an effective support system that meets international human rights standards. The article analyzes issues such as the lack of specialized rehabilitation programs, the fear of reporting crimes due to low levels of trust in law enforcement agencies, and the fragmentation of existing support measures. The possibility of adapting the Panzi model in Ukraine is proposed, which involves integrating victim assistance into the general system of health services, reducing the risk of stigmatization, and creating a sustainable support infrastructure. Special attention is paid to the need for information campaigns and training programs for law enforcement and military personnel on detecting, preventing, and responding to cases of sexual violence. The implementation of an integrated approach can contribute to more effective rehabilitation of victims and strengthening mechanisms for protecting their rights.